2007
DOI: 10.1097/fpc.0b013e3280ef698f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drug transporter genotypes on pravastatin disposition in European- and African-American participants

Abstract: Objective-Our aims were to evaluate the effects of polymorphisms in the hepatic drug uptake transporter organic anion transporting polypeptide 1B1 (OATP1B1, SLCO1B1) and efflux transporters multidrug resistance-associated protein 2 (MRP2, ABCC2), bile salt export pump (BSEP, ABCB11), and breast cancer-related protein (BCRP, ABCG2) on single-dose pravastatin pharmacokinetics in healthy European-and African-American participants.Methods-The pharmacokinetics of a single oral 40mg dose of pravastatin was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
122
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(134 citation statements)
references
References 37 publications
(64 reference statements)
9
122
2
1
Order By: Relevance
“…This suggests that both heterozygous (TC) and homozygous (CC) carriers of the c.521T4C substitution show decreased uptake of atorvastatin into the liver, resulting in increased plasma concentration. These findings are supported by Ho et al, 26 who investigated pravastatin. However, this did not hold true when Pasanen et al 18 Investigated rosuvastatin and found that although the CC genotype resulted in a significant increase in AUC (0À48 h) compared with TT (65%; P ¼ 0.002), only a strong trend was shown for TC versus TT (P ¼ 0.053).…”
Section: In Vivo Pharmacokinetic Studiessupporting
confidence: 80%
See 2 more Smart Citations
“…This suggests that both heterozygous (TC) and homozygous (CC) carriers of the c.521T4C substitution show decreased uptake of atorvastatin into the liver, resulting in increased plasma concentration. These findings are supported by Ho et al, 26 who investigated pravastatin. However, this did not hold true when Pasanen et al 18 Investigated rosuvastatin and found that although the CC genotype resulted in a significant increase in AUC (0À48 h) compared with TT (65%; P ¼ 0.002), only a strong trend was shown for TC versus TT (P ¼ 0.053).…”
Section: In Vivo Pharmacokinetic Studiessupporting
confidence: 80%
“…3,[21][22][23] Similarly, in vitro studies of multidrug resistanceassociated protein 2 have shown that this protein transports a number of statins, 24 but in vivo pharmacogenomic evidence is inconclusive and limited to two small pharmacokinetic studies using pravastatin; these studies obtained contrasting results. 25,26 In contrast, the c.421C4A SNP in ABCG2 has been shown to alter the in vivo pharmacokinetics of both rosuvastatin 27,28 and atorvastatin, 27 although not pitavastatin 29 or pravastatin. 26 Both multidrug resistanceassociated protein 2 and breast cancer resistance protein are reviewed elsewhere by Ieiri et al 19 and although it is accepted that these and other transporters, both intestinal and hepatic, may play a role in statin disposition, this review will focus exclusively on OATP1B1, an hepatic influx transporter that is becoming increasing linked with differences in response to statin therapy.…”
Section: Hepatic Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the UGT1A1 gene, recent studies have suggested the possible association of the adenosine triphosphate-binding cassette C2 (ABCC2) gene and the solute carrier organic anion transporter 1B1 (SLCO1B1) gene with serum bilirubin levels. [37][38][39] In our association study with serum total bilirubin levels, three SNPs within the ABCC2 gene (rs4148386, rs4148396 and rs2145852) and three SNPs within the SLCO1B1 gene (rs4149025, rs4149014 and rs4149018) showed P-values under 0.01, which were, however, far above the significance level after Bonferroni correction (data not shown). No genes except for UGT1A1 were clearly associated with serum total bilirubin levels.…”
Section: Discussionmentioning
confidence: 65%
“…Association studies with polymorphic data from linked loci suggest that diplotype constitution, which characterizes the subset of every single-locus genotype in a gene and is representative of the type of chromosome pairs in an individual, (27,28) could be major determinants of phenotypes. (29) In the present study, homozygosity for the reference allele at the CBR1c.627C>T and +967G>A loci was observed to be associated with increased clearance and reduced exposure levels of doxorubicin in Asian breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%